Diagnostic value of some biochemical indexes of blood and urine (overview information) - Вікуліна, Г. В.; Боровков, С. Б. (Scientific Progress & Innovations, 2017)
In the article we gave literary data about informativity and practical application of biochemical indexes of blood and urine that are calculated using often applied diagnostic criteria of biochemical analysis. As biochemical indexes we examined correlation of indexes of protein metabolism and system of residual nitrogen, enzymes, indexes of exchange of glucose and glycolytic processes, osmolarity ratio. The listed criteria are studied as specific tests in diagnostics of internal diseases, in particular in humane medicine, and can be useful in work of specialists of veterinary profile.